2000
DOI: 10.1364/ao.39.001032
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed indirect photoacoustic spectroscopy: application to remote detection of condensed phases

Abstract: The technique of pulsed indirect photoacoustic spectroscopy is applied to the examination of free liquid surfaces, and the prospects are assessed for remote detection and identification of chemical species in a field environment. A CO(2) laser (tunable within the 9-11-microm region) provides pulsed excitation for a variety of sample types; the resulting photoacoustic pulses are detected at ranges of the order of a few centimeters. The phenomenon is investigated as a function of parameters such as temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Since the 21st century, LPAS has been gradually used in open-path detection, but it was subjected to the large size, heavy-weight, MIR laser sources, i.e., high power OPO or CO 2 lasers, etc. [139,140]. With the development of laser technology in recent years, especially the availability of commercialized QCLs and ECQCLs, LPAS has been becoming a research hotspot to achieve standoff measurement by using QCL/ECQCL as a light source and deforming traditional measurement structures [141].…”
Section: Laser Photoacoustic Spectroscopy (Lpas)mentioning
confidence: 99%
“…Since the 21st century, LPAS has been gradually used in open-path detection, but it was subjected to the large size, heavy-weight, MIR laser sources, i.e., high power OPO or CO 2 lasers, etc. [139,140]. With the development of laser technology in recent years, especially the availability of commercialized QCLs and ECQCLs, LPAS has been becoming a research hotspot to achieve standoff measurement by using QCL/ECQCL as a light source and deforming traditional measurement structures [141].…”
Section: Laser Photoacoustic Spectroscopy (Lpas)mentioning
confidence: 99%
“…The evolution of heat at the solid-air interface relies on sample properties including the absorption coefficient and the thermal diffusivity. 7,[9][10][11] The absorption coefficient determines the heated depth and temperature rise of the solid sample. The thermal diffusivity (a ¼ K/pC p ) determines the heat flow through the system, where K is the thermal conductivity, C p is the heat capacity, and p is the solid density.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the photoacoustic signal decays by 1/ r with detection distance, compared with 1/ r 2 for other spectroscopic techniques. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…One earlier study, which the author named PADAR (photoacoustic detection and ranging), demonstrated standoff detection and ranging for gas vapors using PA effect 6 . In later years PA spectroscopy was also applied to condensed matter and liquids for standoff detection and sensing 7,8 .…”
Section: Introductionmentioning
confidence: 99%